Street nanotexturing of n‐GaN for enhancing light extraction in GaN LEDs. (1st July 2017) - Hsu, Chia‐Liang; Kumar, Amarendra; Kashyap, Kunal; Hou, Max Ti‐Kuang; Yeh, Jer‐Liang Andrew
Abstract : The output power of conventional light‐emitting diodes (LEDs) is enhanced by 9% at 120 mA current without alterations to the existing fabrication techniques and to the multi‐quantum well (MQW) junction. The output power is improved by nanotexturing the street of the n‐gallium nitride (GaN) layer that was unexploited, for the enhancement of the optical or electrical properties. The nanotextured street enhances the light extraction exclusively near the street of the n‐GaN layer by reducing the reflections from the LED surface. Similar light output patterns and I–V characteristics for LEDs with and without street nanotexturing were observed, confirming that the enhanced light extraction has been achieved without a change in the spatial distribution of light or in the properties of the MQW junction. A new approach for the output power enhancement of all types of existing LEDs is provided.